A study on the characteristics of roof wind field by wind tunnel test. (November 2021) - Zou, Qiong; Li, Zhengnong; Zou, Feng; Zeng, Xuan; Wang, Chao; Pan, Yueyue
Abstract: More and more solar-powered devices are installed on roofs, and wind load is its structural design control load. Therefore, roof wind field condition is considered to be the most important prerequisite in studies of wind load on structures. In this study, wind tunnel testing was carried out to observe the roof wind field characteristics of a multistorey building. The change rule and characteristics of the multistorey building roof wind field, under different wind directions were studied, and the roof wind field and ground wind field were then compared. The analysis showed that the closer to the roof, the greater the roof wind field effect on the building. When the distance from the roof Z  ≥ 9 m, it appears that changes in roof wind speed and turbulence intensity are not affected by the building. When the height from roof Z  ≤ 5 m, a turbulence intensity enlargement ratio Δ S I of 0.1–0.3 is recommended. For practical application, a speed-up ratio of the mean wind speed Δ S V of 0.9 is recommended. Highlights: The wind tunnel test is carried out to study the characteristics of roof wind field. The wind speed and turbulence intensity are not affected by the building when Z  ≥ 9 m. When Z  ≤ 5 m, the enlargement ratio Δ S I is recommended to be 0.1–0.3. The speed-up ratio of the mean wind speed on the roof Δ S V is recommended to be 0.9. The conclusions can provide references for structural wind resistance design of roof equipment.